Pensamento pós-crítico, currículo e teoria crítica aproximações, tensões - Barbosa, Renata Peres (Editora Oficina Universitária, 2022)
The proud appreciation of cultural particularisms in the educational field is far from constituting a problem-free paradigm for educators to think about, and it is precisely this weakness of the postmodern agenda that Renata Peres Barbosa proposes to present and intellectually tension. For this purpose, the author has a very consistent theoretical instrument, which is based on the reflections of philosophers of the Frankfurt School, especially Theodor Adorno, who is one of its most important thinkers. The author's central argument consists of the thesis that postmodernity, in its feverish activity of contesting Western universality, ended up producing irrationalist effects, given its tendency to fetishize difference as the indisputable core of liberation from repressed particularisms. From Adorno's perspective, Renata exposes the need for a dialectical confrontation between cultural particularities and universal concepts, with the aim of preserving difference in its condition of non-identity. SINESIO FERRAZ BUENO